Workplace Bullying as a Predictor of Organizational Commitment: Unveiling the Mediating Role of Mobbing - Hamna; Masood, Fahria (Applied Psychology Review, 2025)
The current research aimed to study the relationship between workplace bullying, mobbing and organizational commitment in employees. The study used quantitative correlational research design to examine the relationship between mobbing, workplace bullying, and organizational commitment. Non-probability purposive sampling strategy was used to recruit the sample of N = 150 from national and multinational company employees of Lahore. Workplace Bullying Scale EAPA-T, Luxembourg Workplace Mobbing Scale and TCM Employee Commitment Survey were used for data collection purpose. Pearson Product Moment Correlation Analysis was run to investigate the relationship among workplace bullying, mobbing and organizational commitment. Test of mean differences was used to identify the effect of multiple groups of a demographic variable on the dependent variable. Multiple Hierarchical Regression Analysis was used to find out the mediating role of mobbing in relationship between workplace bullying and organizational commitment. Results indicated that there was a negative correlation of workplace bullying and mobbing with organizational commitment. Workplace bullying negatively predicted organizational commitment. There was a partial mediation of mobbing between workplace bullying and organizational commitment. There were no gender differences in these three variables. This study provides an insight that organizational commitment can be increased by handling workplace bullying and mobbing.